2018
DOI: 10.1111/ijfs.14062
|View full text |Cite
|
Sign up to set email alerts
|

The effects of extruded black rice flour on rheological and structural properties of wheat‐based dough and bread quality

Abstract: Addition of raw black rice flour leads to deficient processability on bread making quality. One of the effective methods to modify the functional properties of black rice flour (BRF) composite dough is to extrude black rice flour (EBRF) before incorporation. This study investigated and compared the effect of BRF and EBRF addition level of 10%-50% on the rheology, microstructure of dough and bread quality. The rheological properties of composite dough were recorded by Mixolab, stress relaxation and tensile test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…With the increased preheat treatment time, the interaction between gluten and gelatinized starch granules was promoted, thus forming a more uniform and compact starch‐gluten network with little gaps. This phenomenon was similar to previous study which found a more cross‐linked microstructure of WF‐EBRF dough (consisting of wheat flour and extrude black rice flour), as starch granules lost their integrity and formed a paste as a function of heating‐extrusion (Ma et al., 2018). As speculated from the SEM images, the protective effect of PPHD was possibly ascribed to its ability to develop a reinforced starch–gluten structure.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…With the increased preheat treatment time, the interaction between gluten and gelatinized starch granules was promoted, thus forming a more uniform and compact starch‐gluten network with little gaps. This phenomenon was similar to previous study which found a more cross‐linked microstructure of WF‐EBRF dough (consisting of wheat flour and extrude black rice flour), as starch granules lost their integrity and formed a paste as a function of heating‐extrusion (Ma et al., 2018). As speculated from the SEM images, the protective effect of PPHD was possibly ascribed to its ability to develop a reinforced starch–gluten structure.…”
Section: Resultssupporting
confidence: 91%
“…In general, all PPHD samples prevented the deterioration rate during freezing and bread made from moderate partial preheat treatment represented better quality. This interesting outcome was possibly related to that gelatinized starch could subserve a continuous network for gas retention (Ma et al., 2018), and the effect of PPHD‐15 min probably resulted from less available free water which led to an underdeveloped gluten network and smaller specific volume (Andrzej et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…[8] In this respect, extruded flours can replace pregelatinized starch or hydrocolloids to increase bread qualities. [9] The effects of extruded black rice flour, [10] sorghum, [11] finger millet, [12] mung bean flour, [13] and wheat bran [14] on technological, textural, and sensory properties of baked bread or noodle have been demonstrated previously. However, it remains challenging to evaluate the real effect of extruded flour on dough properties and product quality because of different ingredients, water addition content, and making process.…”
Section: Introductionmentioning
confidence: 78%
“…The morphology of the dough was observed using a scanning electron microscope (Nova NanoSEM‐450, EI) according to the method of Ma et al (). Small portions of sample were cut with a razor blade and immersed in 4% glutaraldehyde at 4°C for 12 hr or more; then dipped four times with phosphate buffer pH 6.8 at a concentration of 0.1 mol/L for 10 min; after rinsing, embedded in a graded ethanol series (30%, 50%, 70%, and 90%) for 15 min at each gradation; and then embedded in 100% ethanol for 30 min three times.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that extruded wheat bran and wheat germ improved dough stability and bread qualities (Gómez, González, & Oliete, 2012;Gómez et al, 2011). Ma et al (2018) found that the dough with extruded black rice showed more viscous behavior, higher resistance, and extensibility, and the bread with extruded black rice had higher specific volume, lower bake loss, and firmness. Extrusion cooking could also improve the flavor and the overall acceptability of extruded sorghum-wheat composite bread (Jafari, Koocheki, & Milani, 2018b).…”
mentioning
confidence: 99%